Indirubin combined with umbilical cord mesenchymal stem cells to relieve psoriasis-like skin lesions in BALB/c mice - Lu, XiaoJuan; Wang, Hao; Wang, Hongwei; Xie, Fan; Jiang, Cuibao; Shen, Danpeng; Zhang, Hongpeng; Yang, Jie; Lin, Youshu (Frontiers in Immunology, 2022)
Objective: To investigate the efficacy of indirubin combined with human umbilical cord mesenchymal stem cells (hUC-MSCs) in the treatment of psoriatic lesions in BALB/c mice and to explore the related mechanism of indirubin in the treatment of psoriasis. Methods: A BALB/c mouse psoriasis model induced by imiquimod was established and randomly divided into the control group, model group, indirubin group, hUC-MSCs group, and indirubin combined with hUC-MSCs group. Psoriasis area and severity index (PASI) score was used to observe skin lesion changes in the psoriasis-like mouse model. The epidermal scale, the degree of keratinization, and the infiltration of inflammatory cells were observed by HE staining. The concentrations of TNF-α, IFN-γ, IL-17A, and IL-23 in serum of mice were measured using enzyme-linked immunosorbent assay (ELISA). Results: The PASI integral trend chart indicates that hUC-MSCs and indirubin and the combination of drugs could relieve the appearance of skin lesions and accelerate the recovery of skin lesions. The indirubin group had the best effect in improving the scale of skin lesions. HE staining showed that the number of parakeratosis cells in the three treatment groups was significantly reduced, the degree of erythrocyte extravasation dermis hyperplasia and inflammatory cell infiltration was significantly lower than that in the model group, and the skin thickness and spleen index of the combined treatment group exhibited the most noticeable improvement. ELISA showed that the concentrations of TNF-α, IFN-γ, IL-17A, and IL-23 in serum of mice in the hUC-MSCs treatment group, indirubin group, and combined administration group were all decreased compared with those in the model group, and the concentrations of IFN-γ, IL-17A, and IL-23 could be decreased significantly in the indirubin group. Conclusions: Both hUC-MSCs and indirubin can effectively reduce psoriasis-like lesions in BALB/c mice, and the combined administration of these drugs has the best effect.